Optimizing the Hub of Knowledge: Library Management Strategies and Their Role in Enhancing Students' Reading Interest - Annisa Nurfadilah; Subandi; Nina Ayu Puspita Sari (Journal of Educational Management Research, 2026)
This study aimed to examine efforts to optimize library management in fostering students’ reading interest. A descriptive qualitative approach was employed. Data were collected through direct observation, interviews with key informants, and document analysis. The informants consisted of the head of the library, the vice principal for curriculum affairs, and eleventh-grade students. Data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that library management optimization was implemented through four main aspects: collection quantity, collection management, library spatial arrangement, and literacy programs. The library collection was considered adequate, although students’ independent visitation rates remained relatively low. Collection management was conducted systematically and supported by digital library services; however, the availability of general reading materials still requires improvement. The library environment was found to be comfortable, clean, and well-organized, despite the need for maintenance of several facilities. Furthermore, structured literacy programs were effective in developing reading habits and enhancing students’ reading interest. The study implies that effective library management, supported by adequate resources and sustainable literacy programs, can contribute significantly to strengthening students’ reading culture and interest.